Republic of Armenia : Technical Assistance Report-Government Finance Statistics. - International Monetary Fund. Statistics Dept. (Washington, D.C. : International Monetary Fund, 2022)
The mission to Armenia took place between September 27-October 8, 2021 to assist the authorities to improve their Government Finance Statistics (GFS) compilation practices. The technical assistance (TA) mission was conducted by Ms. Ivana Jablonska and Mr. David Bailey at the request of the Ministry of Finance (MOF) and with the support of the IMF's Middle East and Central Asia Department (MCD). The main objectives of the mission were to assist the authorities in finalizing a comprehensive sectorized list of all public sector units -known as, the public sector institutional table (PSIT) - and in compiling annual general government GFS data for 2020.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy; Money and Monetary Policy